Gauging interventions for sustainable travel: A comparative study of travel attitudes in Berlin and London. (October 2015) - Kandt, Jens; Rode, Philipp; Hoffmann, Christian; Graff, Andreas; Smith, Duncan
Highlights: We segment travellers into attitudinal types based on travel and related attitudes. We consider ICT, car sharing, electric cars and residential choices. Six attitudinal segments that are comparable across Berlin and London emerge. The segments differ in potential uptake of sustainable modes and mobility services. Segment-specific interventions to promote sustainable travel are proposed. Abstract: So-called 'soft' policy instruments that respond to the psychological aspects of travel are regularly acknowledged as necessary complements to 'hard' infrastructure investments to effectively promote sustainable travel in cities. While studies investigating subjective orientations among travellers have proliferated, open questions remain including the role of recent technological advances, the expansion of alternative mobility services, locally specific mobility cultures and residential selection. This paper presents the methods, results and policy implications of a comparative study aiming to understand mobility attitudes and behaviours in the wider metropolitan regions of Berlin and London. We specifically considered information and communication technology (ICT), new types of mobility services such as car sharing, electric cars and residential preferences. In each region, we identified six comparable segments with distinct attitudinal profiles, socio-demographic properties and behavioural patterns. Geocoding of the home address of respondents further revealed varying contextual opportunities and constraints that are likely to influence travel attitudes. We find that there is significant potential for uptake of sustainable travel practices in both metropolitan regions, if policy interventions are designed and targeted in accordance with group-specific needs and preferences and respond to local conditions of mobility culture. We identify such interventions for each segment and region and conclude that comparative assessment of attitudinal, alongside geographical, characteristics of metropolitan travellers can provide better strategic input for realistic scenario-building and ex-ante assessment of sustainable transport policy.